Operator controlled, vehicle-based highway crack-sealing machine. (1st January 2003) - Velinsky, S.A.; Feng, X.; Bennett, D.A.
This paper presents a new heavy vehicle system developed for the automated sealing of cracks in highway pavement. The machine has been developed based on the authors' experience over the last twelve years building such machines. A special sealant applicator that deploys a pressurised reservoir was developed to allow for high-speed, automated sealing operations. A telescoping long-reach robotic arm was developed, which can position the sealing head mounted to its end in a 3.65 m (12 ft) by 4 m (13 ft) large workspace within 0.4 mm (1/64 in) at a traverse speed up to 1 m/s (3 ft/s). To ensure adequate sealant flow, a special electrically heated hose was developed. A control network of both fast 100 Mbps Ethernet and 10 Mbps Wireless allows for distributed real-time motion control, I/O control and machine vision. A fully object-oriented, multi-threaded and Internet-based software architecture allows reliable and efficient system integration and provides an interactive and responsive user interface for feature-rich and easy imaging, path planning and system control. An operator-assisted crack identification method is used and the path planning method is based on simulated annealing in order to optimally seal a network of cracks.